The Influence of Principals' Digital Leadership on Teacher Readiness in the Digital Transformation of Education - Nursalimah Nursalimah; Riska Meisyi Putri; Dismawati Dismawati; Mardalena Mardalena; Sarinah Sarinah (Al-Qalam Institue, 2026)
The digital transformation of education requires teachers' readiness to integrate technology into the learning process. This readiness is not only influenced by individual factors, but also influenced by organizational support, including the leadership role of the principal. This study aims to analyze the influence of school principals' digital leadership on teachers' readiness in the digital transformation of education. The research uses a quantitative approach with an explanatory research design. The research sample consisted of 50 elementary school teachers in Merangin Regency, Jambi Province who were selected using the purposive sampling technique. Data were collected through a Likert scale questionnaire and analyzed using descriptive statistics and simple linear regression. The results showed that the digital leadership of school principals was in the high category with an average score of 30.50, while teacher readiness was also in the high category with an average score of 31.08. The results of the regression test showed that the digital leadership of school principals had a positive and significant effect on teacher readiness (β = 0.875; t = 12.516; p < 0.05). The value of the determination coefficient (R² = 0.765) showed that digital leadership contributed 76.5% to teacher readiness. These findings affirm the importance of strengthening the digital leadership of school principals in supporting the success of digital transformation of education.